Ảnh hưởng của đổi mới dịch vụ và hành vi cùng tạo ra giá trị đến trải nghiệm của khách du lịch - Lê Minh , Đức (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This research examines the impact of service innovation and co-creation on customer experience (emotion experience, well-being, and memorability). A total of 335 responses gathered from tourists were assessed using structural equation modeling (SEM). The results show that service innovation significantly influences co-creation, customers’ emotional experience (pleasure and arousal), and well-being. The findings continue to reveal the positive effect of co-creation on the emotional experience and memorability of the experience. In particular, the customers’ co-creation is associated with customers' well-being. This is an interesting finding. In addition, customers' emotional experience has a positive impact on both well-being and memorability. Furthermore, customers' well-being has a positive link to the memorability of their experience. Some practical and theoretical implications of this outcome to the marketing and tourism industries are discussed.
Keywords: Service-Dominant logic; Service innovation; Customer value co-creation behaviors; Emotion experience; Well-being; Memorability